PENGARUH UKURAN PERUSAHAAN, DISCLOSURE, DAN AUDIT DELAY TERHADAP OPINI AUDIT GOING CONCERN - Kanya Alfani (2020)
The implementation of this research is to determine and analyze the impact of firm size, disclosure, and audit delay on going concern audit opinion. This research uses quantitative research methods. The data in this study use secondary data. The population in this study all manufacturing companies listed on IDX in the period 2016 - 2018. The sample used is 131 company. Logistic regression analysis method used in this study. The results in this study indicate that firm size has a significant effect on going concern audit opinion, disclosure has a significant negative effect on going concern audit opinion and audit delay has no significant effect on going concern audit opinion.